PsycEXTRA Dataset
DOI: 10.1037/e523202010-001
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a Short-Acting Benzodiazepine on Brain Electrical Activity During Sleep

Abstract: 1, SUMMARYThe changes seen in EEG activity with administration of long-acting benzodiazepines are a significant decrease In delta, 0.5-3 Hz, and a significant increase in sleep spindles, bursts of 11-15 Hz activity. These changes often persist for several days after the medication is discontinued.The introduction of a new benzodiazepine hypnotic, triazolam, in which the half-life of both the parent compound and its metabolite is less than 10 hours, raises questions as to whether its use will produce similar EE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 12 publications
1
3
0
Order By: Relevance
“…Unlike the progressive increases in beta activity across drug nights, sigma enhancement peaked immediately on the IDN for each BDZ and did not change significantly across the drug nights, except HAX which showed significances when 4DN and 7DN were compared with IDN. Thus, sigma enhancement appeared less related to plasma accumulations of these BDZ hypnotics, which is consistent with previous reports 19,20 . Although FNZ produced a distinctly peaked large enhancement in beta activity during REM periods as we previously reported 11 it was not significantly greater than that produced by HAX or TRI.…”
Section: Discussionsupporting
confidence: 93%
“…Unlike the progressive increases in beta activity across drug nights, sigma enhancement peaked immediately on the IDN for each BDZ and did not change significantly across the drug nights, except HAX which showed significances when 4DN and 7DN were compared with IDN. Thus, sigma enhancement appeared less related to plasma accumulations of these BDZ hypnotics, which is consistent with previous reports 19,20 . Although FNZ produced a distinctly peaked large enhancement in beta activity during REM periods as we previously reported 11 it was not significantly greater than that produced by HAX or TRI.…”
Section: Discussionsupporting
confidence: 93%
“…Presleep heart rate (HR) was calculated by counting heart beats on the polygraphic record, obtaining 1-min samples every 2 min from the time of lights out to Stage 2 onset. Spindle rates and delta rates during sleep were obtained according to procedures described previously (Johnson & Spinweber, 1981; Johnson, Spinweber, Seidel, & Dement, 1983). Following the morning awakening, subjects were asked to estimate their laboratory sleep latencies and evaluate their nighttime sleep by responding to our Morning Questionnaire.…”
Section: Methodsmentioning
confidence: 99%
“…In our previous research on sleeping aids (Johnson & Spinweber, 1981; Spinweber & Johnson, 1982, 1983), we utilized questionnaire responses and laboratory polysomnography to select sleep-onset insomniacs for participation. On the Naval Health Research Center (NHRC) Sleep Questionnaire (Johnson & Spinweber, 1983), potential subjects identified themselves as poor or very poor sleepers, reported a usual sleep latency of at least 45 min and indicated that they had trouble falling asleep for over 6 months.…”
mentioning
confidence: 99%
“…In both parts ofthe present study, this led to an increase in stage 2 of 59 % under lormetazepam and 68 % under triazolam (KaIes et al, 1976;Leibowitz and Sunshine, 1978). However, under benzodiazepines the increase in stage 2 is accompanied by an increase in spindie density, i.e., in sleep spind-Ies per minute of stage 2 (Borbely et al, 1983;Johnson and Spinweber, 1981 ;Johnson et al, 1983;MOn/i, 1981 ;Spinweber and Johnson, 1982). While spindie reduction rarely exceeded normal values to any significant extent under land 2 mg lormetazepam, it was 42 % above the norm under 0.5 mg triazolam and as much as 65 % above the norm under I mg.…”
Section: S/eep Spind/esmentioning
confidence: 99%